Concrete : architecture & design - Roth, Manuela. 4 0 16; 5 (Salenstein, Switzerland : Braun Publishing, 2011)
Hardly any other material unites such contradictory associations, stigmatised on the one hand, celebrated on the other: concrete is still in the spotlight. Its almost inexhaustible potential and ever new applications and possibilities make it a most valuable building material.
Includes index.
Keywords: 2 -- 0; 6; Design and construction.;Pictorial works. -- Concrete construction;Architecture, Modern -- 21st century; 20; 2